A comparison of the heat stability of fresh milk protein concentrates obtained by microfiltration, ultrafiltration and diafiltration. Issue 3 (12th July 2019) - Renhe, Isis Rodrigues Toledo; Zhao, Zhengtao; Corredig, Milena
Abstract: The objective of this work was to evaluate the impact of changes during membrane filtration on the heat stability of milk protein concentrates. Dairy protein concentrates have been widely employed in high protein drinks formulations and their stability to heat treatment is critical to ensure quality of the final product. Pasteurized milk was concentrated three-fold by membrane filtration, and the ionic composition was modified by addition of water or permeate from filtration (diafiltration). Diafiltration with water did not affect the apparent diameter of the casein micelles, but had a positive effect on heat coagulation time (HCT), which was significantly longer (50 min), compared to the non diafiltered concentrates (about 30 min). UHT treatments increased the particle size of the casein micelles, as well as the turbidity of retentates. Differences between samples with and without diafiltration were confirmed throughout further analysis of the protein composition of the unsedimentable fraction, highlighting the importance of soluble protein composition on the processing functionality of milk concentrates.